Long-term Management Effects on Soil Properties and Yields in a Wheat-Soybean Double-Crop System in Eastern Arkansas. Issue 1 (January 2016) - Norman, C. Ryan; Brye, Kristofor R.; Gbur, Edward E.; Chen, Pengyin; Rupe, John
Abstract : Abstract: The sustainability of soil and water resources in regions of highly productive row-crop agriculture depends on long-term implications of agricultural management decisions. Residue management can strongly affect soil organic matter (SOM), soil C, and other near-surface physical and chemical properties in agricultural soils, especially in double-crop systems. The objective of this study was to determine the long-term trends in SOM, soil C and N, bulk density, pH, electrical conductivity, and Mehlich-3–extractable nutrients in the top 10 cm and yield as affected by alternative residue and water management practices in a wheat ( Triticum aestivum L.)-soybean ( Glycine max (L.) Merr.) double-crop production system. The field site resides on a loessial soil (fine silty, mixed, active, thermic Glossaquic Fraglossudalf) in the Lower Mississippi River Alluvial Valley of eastern Arkansas and has been consistently managed for 13 years between Fall 2001 and Fall 2014. Averaged across all other treatment factors, SOM content did not change ( P > 0.05) between 6 and 13 years after conversion to alternative management practices under irrigation, whereas SOM content increased across time ( P < 0.05) until approximately 9 years after initial conversion then decreased thereafter under dryland production. Soil C content generally increased, P content generally decreased, and N and Cu contents and soybean yields changed little across time because of irrigation. Across time, SOM and C contents decreased ( P < 0.05) under residue burning but increased under nonburning. The results of this study indicate that irrigation management and residue burning were responsible for many of the largest differences in near-surface soil property trends across time. Understanding the long-term effects of alternative, compared with traditional, management practices is critical to developing sustainable agricultural practices in the mid-southern United States.